Precipitation of struvite using MgSO4 solution prepared from sidestream dolomite or fly ash. Issue 12 (December 2022) - Pesonen, Janne; Janssens, Fien; Hu, Tao; Lassi, Ulla; Tuomikoski, Sari
Abstract: Struvite (NH4 MgPO4 ∗6H2 O) is a slow-release fertilizer produced from phosphorus and nitrogen-containing wastewater in the presence of Mg salts. Commercial Mg salts are the single most significant cost of struvite precipitation. In this study, H2 SO4 formed as an industrial sidestream was used to prepare MgSO4 solution from waste dolomite (DOL) and fly ash (FA). MgSO4 solution was then used to precipitate struvite from a synthetic (NH4 )2 HPO4 solution and from actual industrial process waters. The best results were obtained with real process waters where over 99% of phosphate and about 80% ammonium removals were achieved with both MgSO4 solutions after 30 min of reaction time. A higher molar ratio between Mg and P improved the phosphate removal efficiency, especially with DOL-based MgSO4 solutions; however, it had no practical effect on ammonium removal. The struvite content of precipitates was 75.49% with an FA-based chemical and 60.93% with a DOL-based chemical; other valuable nutrients (Ca, K, S, Fe, Mn, and Cl) were captured in the precipitates. The results indicate that both sidestream-based reagents perform well in struvite precipitation and that the formed precipitates could be used as fertilizers. Graphical abstract: Image 1 Highlights: Mg-containing precipitation chemicals were prepared from industrial sidestreams. An Mg solution was used to uptake nitrogen and phosphorus with good results. More than 99% of phosphate removals were achieved from process waters. The precipitates contained struvite and could be used as fertilizers. Abstract : Dolomite; Fly ash; Phosphate; Struvite; Precipitation; Circular economy; Water treatment/